Legal Analysis of the Application of the Principle of Balance in Marriage Agreements (Study of Supreme Court Decision Number 1362 K/Pdt/2024) - Patrick Fransseda Naibaho; Janpatar Simamora; Roida Nababan (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
This study aims to analyze the regulation and implementation of marital agreements under the Indonesian Marriage Law and to examine the legal considerations of the Supreme Court in Decision Number 1362 K/Pdt/2024. This research employs a normative juridical method. The findings indicate that in Decision Number 1362 K/Pdt/2024, the Supreme Court affirmed that a prenuptial agreement containing an imbalanced clause where all marital assets become the wife’s property while all obligations are imposed upon the husband contradicts the principle of balance (the principle of equality). This decision emphasizes that freedom of contract in marital agreements is not absolute, but must be limited by the principles of substantive justice and the protection of the weaker party.